Windows Vista: Securing Itself against Competition? - Georg Erber; Stefan Kooths (Weekly Report, 2007)
About the end of 2006, Microsoft began delivering its new Windows Vista PC operating system to large commercial customers, followed by final users and small businesses. Even before the product reached the market, the dominant provider of PC operating systems worldwide was accused over and over of abusing its market power in order to hinder competitors. After the integration of Internet Explorer (Windows 95) and the Windows Media Player (Windows XP), competitors today are objecting most strongly to the new security components associated with the Windows Vista Security Center, and the EU Commission has joined in these objections. Opponents have criticized the bundling of previously independent components (transfer of market power through bundling), and security software providers like Symantec and McAfee have argued that limiting access to the core of the operating system will hinder their product development activities. In line with the tradition in EU competition policy, Microsoft's dominance of the PC operating system market justifies supervision of that provider in the interests of preventing abuse. However, the final assessment must take into account unique circumstances arising from the specific market and competitive conditions in the standard software markets. In particular, competition policy should intervene in the PC operating system market only if a demonstrable improvement in the public welfare can be attained as a result. In essence, this means that policymakers should intervene to ensure fair innovation competition, including the introduction of reasonable transparency requirements with respect to operating system interfaces in order to allow regulators to manage potential conflicts between the operating system manufacturer and providers of competing software components (e.g. web browsers, media players or security software). There is need for reform in this area in order to create a reliable and functional system of rules for all market participants. However, unbundling decrees which require strict separation of certain system components are an unsuitable instrument for this purpose.
Keywords: K21; L41; L42; L63; 330; competition policy; Microsoft; operating system markets; platform competition